Process control of paper web heating on the basis of dynamic programming method - Черьопкін, Євгеній Сергійович; Жученко, Анатолій Іванович (Technology audit and production reserves, 2015)
This paper deals with the use of dynamic programming method for the creation of optimal process control of paper web heating in the drying part of the paper machine, Results of the synthesized system are given. The main aim of research is to establish the efficiency of dynamic programming method under the influence of various sizes of disturbances on the control object. Using the method of simulation modeling it is conducted experimental researches of developed control system with the implementation of dynamic programming method adapted to this process. The proposed software solution allows effectively control the process of paper web heating in a wide range of disturbances. Dynamic programming method, which was implemented in the work, allows calculating the optimal values of control actions in each drying cylinder, which leads to solving the problem of process control while minimizing control criteria. The proposed solution can be used as part of the overall control process of the paper web drying in the drying part of the paper machine. The results will be used in the future to modify the dynamic programming method to integrate into it elements of prediction of perturbations and real-time correction of control actions.